OPTIMASI PRODUKSI SUCKER ROD PUMP PADA SUMUR HCP LAPANGAN PSN - Hanadry Charlin Pasanea; Edi Untoro; Roy R. Lekatompessy (Department of Mechanical Engineering, 2025)
Oil and gas are important resources that every country must fulfill and Indonesia, despite being a producer, has not been able to meet domestic demand. In field operations, wells do not always produce optimally, so an evaluation and optimization of pump performance is needed to produce optimal production rates. Research on the evaluation of the Sucker Rod Pump at Well M has been carried out by Untoro, E & Saleky, H (2023), obtained the results of the flow rate (Qmax) of 945.403 Bfpd, the current Q of 236.63 Bfpd, pump displacement (v) of 792.091091 Bfpd, and pump volumetric efficiency of 29.87497%. Thus, from the evaluation results, this research will optimize the Sucker Rod Pump, with the aim of obtaining Sucker Rod Pump optimization results to obtain the optimal production rate. Optimization was carried out by changing the pump SPM from 6 SPM to 8 SPM and the pump stroke length from 150 in to 145 in, so that the production rate increased from the previous 236.63 Bfpd to 355,3 Bfpd, and the pump volumetric efficiency increased to 34,77%. Keywords: Sucker Rod Pump, Optimization, Artificial Lift